THE EFFECT OF RETURN ON ASSETS, COMPANY SIZE, INDEPENDENT COMMISSIONERS, AND CAPITAL INTENSITY ON EFFECTIVE TAX RATE - Haznadila Aulia Sanyora; Nasrizal; Devi Safitri (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This study analyzes the effect of return on assets (ROA), company size, independent commissioners, and capital intensity on the effective tax rate (ETR). The population of this study consists of mining sector companies listed on the Indonesian Stock Exchange from 2017 to 2021. The samples of this study consist of 19 companies which were chosen by purposive sampling technique based on the specific criteria. This study uses secondary data obtained from the company's financial statement and annual report. The data analysis used is a multiple linear regression method. The finding of this study shows that return on assets and capital intensity negatively affect the effective tax rate. Company size was found to have a positive effect on the effective tax rate. Meanwhile, the independent commissioners do not affect the effective tax rate.